Hormonalna terapia zastępcza a cukrzyca - Wender-Ożegowska, Ewa; Ożegowska, Katarzyna; Gutaj, Paweł (Menopause Review/Przegląd Menopauzalny, 2013)
The purpose of the study is to present today’s opinions on hormonal replacement therapy among women with diabetes. Actual knowledge demonstrates that there are no contraindications for HRT in diabetes. This therapy has no adverse effect on glycemic metabolism in diabetic women and selected preparations have a positive effect. Some forms improve the lipid profile in this population. It seems that transdermal therapy containing 17-beta estradiol and natural progesterone or NETA may be the preferable method of treatment recommended for diabetic patients. Nowadays, the use of HRT for the prevention or treatment of CVD is unclear and women should be informed about these data before starting the therapy. This should not stop doctors from prescribing HRT to diabetic women mainly for menopausal symptoms and for the prevention of osteoporosis. On the basis of the data collected so far, however, it is suggested that the risk-benefit ratio is similar to that for the nondiabetic population. A decision whether to prescribe HRT should always be tailored to the individual. Individual assessment of the potential benefits and risks of HRT treatment should be performed for women with diabetes as it is for all women when HRT is considered.